Foreshock activity and its probabilistic relation to earthquake occurrence in Albania and the surrounding area - K. Irikura; K. Matsumura; V. Peçi; K. Maeda (Annals of Geophysics, 1999)
We investigate some characteristics of foreshock activity of moderate and large earthquakes which occurred in the present century in Albania and the surrounding area. Using a prediction algorithm, based on possible foreshocks, we obtained a probabilistic relation between possible foreshocks and mainshocks. From documentary and instrumental data for the period 1901-1994 for the area between 39.0°- 43.0°N and 18.5°-21.5°E we evaluated the probability of the occurrence of mainshocks immediately after their possible foreshocks. The result shows that the probability that mainshocks with magnitude M ³ 6.0 are preceded by a foreshock with magnitude M ³ 4.4, distance £ about 50 km and time £ 10 days is 38% (6/16). The probability that one earthquake with M ³ 4.4 will be followed by a larger earthquake with M ³ 6.0 within about 50 km and 10 days is 1.3% (6/468), but the probability increases to 33% (1/3) if 7 earthquakes with M ³ 4.4 occur within about 50 km and 10 days. From instrumental data for the period 1971-1994, the probability that mainshocks with M ³ 5.0 are preceded by a foreshock with magnitude M ³ 4.0 is 33% (5/15). The probability that one earthquake with M ³ 4.0 will be followed by a larger earthquake with M ³ 5.0 within about 50 km and 10 days is 1.9% (5/262), but the probability increase to 5.6% (1/18) if 3 earthquakes with M ³ 4.0 occur within about 50 km and 10 days. We also found a regional variation of foreshock activity with activity decreasing from the Vlora-Elbasani-Dibra transversal seismic belt to the Ionian-Adriatic seismic zone to the interior part of Albania seismic zone.